Visible Light‐Mediated Metal‐Free Chlorodifluoromethylation of Arenes and Heteroarenes by a Hypervalent Iodine EDA Complex. Issue 35 (24th June 2022) - Lin, Daniel; Krishnamurti, Vinayak; Prakash, G. K. Surya
Abstract: A novel EDA complex comprised of a bis(chlorodifluoroacetoxy)iodoarene and 1, 3, 5‐trimethoxybenzene is described, which enables the direct radical C(sp 2 )−H chlorodifluoromethylation of arenes and heteroarenes under monochromatic visible‐light irradiation. The procedure is mild, operationally simple, and utilizes commercially available reagents. The developed conditions demonstrate compatibility with a host of commonly encountered functionalities and biologically relevant scaffolds, whilst showcasing the post‐functionalization capabilities of the −CF2 Cl moiety. Various mechanistic studies were performed to explore the EDA complex and radical generation pathway. Abstract : A visible light‐mediated electron donor–acceptor complex enabling direct chlorodifluoromethylation of (hetero)arenes is described. This method provides the privileged moiety with mild conditions across a broad range of functional groups and bioactive scaffolds. Post‐functionalization reactions and key control experiments are reported as well. The core EDA complex is studied spectroscopically, enabling further synthetic applications in the future.